2017
DOI: 10.3758/s13414-017-1289-6
|View full text |Cite
|
Sign up to set email alerts
|

On the value-dependence of value-driven attentional capture

Abstract: Findings from an increasingly large number of studies have been used to argue that attentional capture can be dependent on the learned value of a stimulus, or value-driven. However, under certain circumstances attention can be biased to select stimuli that previously served as targets, independent of reward history. Value-driven attentional capture, as studied using the training phase-test phase design introduced by Anderson and colleagues, is widely presumed to reflect the combined influence of learned value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
127
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(149 citation statements)
references
References 60 publications
13
127
4
Order By: Relevance
“…Consistent with many prior studies, no effects of feedback were evident during the training phase (e.g., Anderson, 2016aAnderson, , 2017Anderson et al, 2011aAnderson et al, , 2014bAnderson et al, , 2016aAnderson & Halpern, 2017), suggesting that performance was dominated by the influence of task goals in this part of the task. However, when goals and attention to valenced stimuli conflict, as in the test phase, a robust attentional bias was evident.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with many prior studies, no effects of feedback were evident during the training phase (e.g., Anderson, 2016aAnderson, , 2017Anderson et al, 2011aAnderson et al, , 2014bAnderson et al, , 2016aAnderson & Halpern, 2017), suggesting that performance was dominated by the influence of task goals in this part of the task. However, when goals and attention to valenced stimuli conflict, as in the test phase, a robust attentional bias was evident.…”
Section: Discussionsupporting
confidence: 85%
“…It is important to distinguish between attentional biases driven by associative learning and attentional biases driven by former target history (Anderson & Halpern, 2017;Sha & Jiang, 2016). In our experimental design, the critical distractors were not only previously associated social feedback during training, but these stimuli were also previously task-relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work showed that attentional capture was rewardbased but was also influenced by the familiarity of previous targets (e.g., Sha & Jiang., 2016, but see Anderson & Halpern, 2017). In the present study, modulations of both alpha power and N2pc amplitude were found following the previously rewarded distractor, compared to a novel color.…”
Section: Discussionsupporting
confidence: 43%
“…The success of this inhibitory process depends on both the physical salience and previous task-relevance of the stimuli. In addition to previous research on location and relation WM tasks, the current study also draws on previous research demonstrating that the previous value of a stimulus can influence the allocation of attention, even when this stimulus is no longer relevant (Anderson et al, 2011Anderson & Halpern, 2017;Rutherford et al, 2010). To study VDAC, previous work relied on a paradigm including a training and a test phase.…”
Section: Introductionmentioning
confidence: 99%
“…On distractor-absent trials, in order to quantify the probability of initially fixating a distractor for the sake of comparison, one of the nontargets was dummy-coded as the critical distractor on each trial using the same parameters that were used to define the position of the critical distractors on distractor-present trials (i.e., same counterbalance of position relative to the target position; note that averaging across all nontarget fixations produces the same pattern of results). A planned comparison focused on the difference in oculomotor capture between high-value and lowvalue distractor trials, given the importance of this comparison in establishing value dependence (Anderson & Halpern, 2017;Sha & Jiang, 2016); Bonferroni correction was applied to the two additional post hoc comparisons (α = 0.025). The probability of fixating a nontarget other than the critical distractor (while accounting for the number of such stimuli on each trial) did not differ across distractor conditions, p = .242, and so was not separately considered for each condition.…”
Section: Discussionmentioning
confidence: 99%